2017
DOI: 10.21512/lc.v11i2.1504
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Needs to Develop English Writing Materials

Abstract: This research explored sophomore students’ needs in learning English writing at the Faculty of Education for Language and Arts, IKIP Mataram. To achieve this purpose, classroom observation, questionnaire, and documentation were conducted to collect data. Data were then analyzed descriptively, and triangulation of data analysis was also carried out. Based on the result of the questionnaire survey, the findings show that the students’ proficiency level is at the elementary level. Moreover, the students’ needs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 6 publications
5
9
0
1
Order By: Relevance
“…The result of the study was in accordance with Sumarsono, Bagis, and Arrafii (2017). Their findings showed that the learners' ability level was at the elementary level.…”
Section: Learning Needs Of the Learnerssupporting
confidence: 78%
“…The result of the study was in accordance with Sumarsono, Bagis, and Arrafii (2017). Their findings showed that the learners' ability level was at the elementary level.…”
Section: Learning Needs Of the Learnerssupporting
confidence: 78%
“…The results of the need analysis are in line with Sumarsono et al (2017) mentioned that 82% of leaners wanted to improve their grammar and vocabulary mastery. Compatible with Sundari et al (2018) wrote that the learners felt difficult in arranging the sentences well.…”
Section: Discussionsupporting
confidence: 78%
“…Many factors influenced by this condition, the internal factor, as a study held by Kurniasih (2013) found that the linguistics aspect became a difficulty for the learners to write well. It probably comes from the external factor such as the learners' lack of learning motivation (Oktarina et al 2018), the materials did not follow the learners' needs (Sumarsono et al 2017), and the learners used general textbooks.…”
Section: Introductionmentioning
confidence: 99%
“…Pertaining to the issue of needs analysis in writing skills, the number of studies conducted in the topic of need analysis is increasing simultaneously such as the analysis of student needs for writing skills materials development (Tjalla, Akil, Hamra & Haryanto, 2017), designing academic writing material (Ampa & Quraisy, 2018;Ghufron, Saleh, Warsono, & Sofwan, 2016;Ibrahim, Ali, Rahman, & Salih, 2013;Shree, Mohd, Nor, & Din, 2014;Sumarsono, Bagis, & Arrafii, 2017;Yundayani, 2017Yundayani, , 2018, a model of instructional material of academic writing (Ghufron et al, 2016;Linh & Suppasetseree, 2016). The current study is a need analysis which is conducted in academic writing to develop academic writing material that matches with the current curriculum and condition of learning writing for the Indonesian university context.…”
Section: Introductionmentioning
confidence: 99%